2020
DOI: 10.3389/fpsyt.2020.00015
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Lower Limb Representations Underlying Vision, Touch, and Proprioception in Body Integrity Identity Disorder

Abstract: Individuals with Body Integrity Identity Disorder (BIID) have a (non-psychotic) longstanding desire to amputate or paralyze one or more fully-functioning limbs, often the legs. This desire presumably arises from experiencing a mismatch between one's perceived mental image of the body and the physical structural and/or functional boundaries of the body itself. While neuroimaging studies suggest a disturbed body representation network in individuals with BIID, few behavioral studies have looked at the manifestat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 101 publications
0
10
0
Order By: Relevance
“…Moreover, individuals with BID reported differences in sensation between the affected and unaffected limb in the direction of both increased (15%) and reduced sensitivity to touch (14%) [ 13 ]. However, when tested systematically, such individuals do not have more tactile perception deficits on the part of the body for which they feel a desire for amputation [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, individuals with BID reported differences in sensation between the affected and unaffected limb in the direction of both increased (15%) and reduced sensitivity to touch (14%) [ 13 ]. However, when tested systematically, such individuals do not have more tactile perception deficits on the part of the body for which they feel a desire for amputation [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Stone and co-workers [ 15 ] demonstrated that individuals with BID have a normal perception of their legs showing a performance comparable with that of the controls in tasks measuring different aspects of body representation: visual perception of the lower limbs (i.e., template matching task: visually-guided judgments of length and width of distorted images of their own legs), tactile perception (i.e., tactile distance estimation task: judgments about the distance between two simultaneously applied tactile stimuli), and proprioceptive body representation (i.e., localization task: asking participants to localize unseen landmarks on their legs). The authors also demonstrated that individuals with BID perform normally in feet mental rotation suggesting the presence of a preserved ability in using the body representation of the affected part during the task [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the situation of caregivers, Eggert et al ( 14 ) provided evidence that one out of three caregivers in Germany reported a worsening of the care situation after the outbreak of COVID-19. Evidence from several countries shows that large proportions of caregivers have experienced an increased burden and stress-related symptoms, like trouble sleeping, since the outbreak of the pandemic [e.g., ( 9 , 13 , 22 , 23 )]. Furthermore, informal caregivers frequently reported worsened physical and mental health, such as being depressed or anxious as well as feeling more socially isolated and lonely [e.g., ( 9 , 24 , 25 )].…”
Section: Introductionmentioning
confidence: 99%
“…Himanshu et al (2020) state that prevalence BDD is on the rise. BDD is an increasingly prevalent condition causing psychological and functional impacts, so recognition and treatment is essential.…”
Section: Prevalence Of Bddmentioning
confidence: 99%